Analisis Keterampilan Berbahasa Inggris di Bidang Industri Pariwisata untuk Pemula - Kanca, I Nyoman (Lembaga Yasin AlSys, 2024)
This study explores the importance of English language proficiency in supporting the development of the tourism industry, especially for beginners in the sector. The approach used is qualitative, with data collection through observation and interviews. Various relevant references, including scientific journals and books related to this topic, were collected and analyzed in depth to answer various questions that emerged in the study. The results of this study indicate that good English language skills are essential for tourism industry players to provide a satisfying experience for guests. This certainly contributes positively to increasing revenue and profits for hotels or tourist destinations. In addition, English language skills also affect job opportunities, career promotions, and improving the positive image of employees in the hotel and other tourism sectors. Given the importance of English language proficiency in the tourism industry, it is very important for the community, government, and educational institutions focusing on the tourism sector, such as vocational schools, tourism colleges, and training institutions, to prepare students with adequate English language skills. This effort can be done by providing more focused and quality English education.